Upaya Peningkatan Kemampuan Interpersonal Melalui Model Pembelajaran Connectin Organizing Reflecting And Extending Pada Mata Pelajaran Akidah Akhlak Kelas Vii Mts Al Washliyah Pangkalan Berandan - Rika Rahayu; M. Hasbullah; Rani Febriyanni (Prodi Pendidikan IPS STKIP AL MAKSUM, 2022)
This research goes directly to the field to obtain data. The approach used is a quantitative approach because the design of this study was carried out using statistical processing numbers. Before the research, questionnaires from the variable (X) and variable (Y) were distributed at MTs Al Washliyah Pangkalan Berandan for a try out test which was distributed to 30 respondents. The results of this study are: (1) The Connecting Organizing Reflecting And Extending learning model on Akidah Akhlak subjects at MTs Al Washliyah Pangkalan Berandan is classified as good, because it has an average of 91.02 which is included in the 91-100 interval. (2) Interpersonal ability of students in the Akidah Akhlak subject at MTs Al Washliyah Pangkalan Andan is classified as good, because it has an average of 73 which is included in the interval 73-80. (3) Based on the results of hypothesis testing, there is an effect of the Connecting Organizing Reflecting And Extending learning model on students' interpersonal abilities in the Akidah Akhlak subject at MTs Al Washliyah Pangkalan Berandan.